DEVELOPMENT OF GAME SEASON EXPLORER USING CONSTRUCT 2 - Tria Suci Cahyani; Dilla Safira; Santika Lana Hayati; Mohamad Bagoes Ali Yuddin; Dodik Arwin Dermawan (LPPM STMIK Pringsewu, 2022)
Children self-taught install many games on their gadgets so they can play in their free time. Because children feel bored, games are a solution for parents to overcome them. In addition to encouraging children's creativity and imagination, playing games can develop skills as well as a means for developing thinking patterns/ problem solving, using children's logic and instincts whose hopes can also develop their talents or abilities and direct them to positive things. With the waterfall method, game development is made manually and in stages starting from the visual background, actors, and other elements in the game, using the construct 2 application as supporting software in game development. The quality of the game based on the results of the questionnaire given to the respondents is in the existing picture. The game